Power output comparison between electronic ballast in induction lamp and power supply unit LED Lamp - Mohd. Saiful Islam Abidin, 1988- , author; Hasimah Abdul Rahman, supervisor; Fakulti Kejuruteraan Elektrik (2012)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2012